Trough s-infliximab and antibodies towards infliximab in a cohort of 79 IBD patients with maintenance infliximab treatment. (1st August 2014) - Marits, Per; Landucci, Laura; Sundin, Ulf; Davidsdottir, Loa; Nilsson, Jakob; Befrits, Ragnar; Wikström, Ann-Charlotte; Eberhardson, Michael
Abstract: Background and Aims: The anti-TNF antibody infliximab is effective in inducing remission in Crohn's disease as well as in ulcerative colitis and many patients are treated for several years with sustained clinical remission. However, the role of monitoring s-infliximab and antibodies towards infliximab during maintenance treatment remains unclear. Our aim was to correlate serum drug levels and antibodies to clinical activity, CRP, albumin and concomitant immunosuppression in a cohort on maintenance infliximab treatment. Methods: We included 79 patients with Crohn's disease or ulcerative colitis who had responded to infliximab and received maintenance treatment (4–69 infusions) in this retrospective study. Infliximab levels and antibodies towards the drug were analyzed with in-house-developed ELISA assays. Results: The mean s-infliximab was significantly higher in patients in remission (4.1 µg/mL) as compared with disease flare (mean 1.8 µg/mL); p < 0.001. The s-infliximab showed a significant negative correlation with Harvey–Bradshaw index (r = - 0.21; p < 0.05). Serum-infliximab progressively decreased with the number of accumulated infusions (p < 0.05). In patients with undetectable trough levels, 55% of the patients with concomitant immunosuppressive were positive for antibodies against infliximab, as compared with 94% of patients on monotherapy. Patients with undetectable serum-infliximab were in clinical remission at 25% of the visits. Conclusions: The trough level 4.1 µg/mL may serve as cut-off for clinical remission. Drug trough levels decreased during treatment and almost all patients with undetectable s-infliximab and monotherapy had developed antibodies against the drug.